2014
DOI: 10.1055/s-0033-1360400
|View full text |Cite
|
Sign up to set email alerts
|

Phyllanthus amarus Does Not Affect Hypernociception in Experimental Autoimmune Encephalomyelitis

Abstract: Multiple sclerosis is an inflammatory disease of the central nervous system. Chronic pain is one of the main symptoms, affecting many patients. Studies show that the lignans or the apolar extracts of Phyllanthus amarus have antinociceptive effects in different animal models. To evaluate the antihypernociceptive effect of a hexanic extract of P. amarus in experimental autoimmune encephalomyelitis in mice, the chemical composition of the hexanic extract was analyzed by gas chromatography mass spectrometry. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…Eleven lignans were identified in the samples analyzed (Table 3), with P. amarus being the only sample in which all eleven were detected and had been all previously detected in other studies (Nahar et al, 2012;Molska et al, 2014;Qi et al, 2014), confirming that it was the major producer of lignans among the studied species. Seven lignans were detected in P. niruri but, only niranthin, hypophyllanthin and dextrobursehernin were detected for the first time (Nahar et al, 2012;Qi et al, 2014).…”
Section: Lignan Content In the Different Phyllanthus Speciessupporting
confidence: 71%
See 3 more Smart Citations
“…Eleven lignans were identified in the samples analyzed (Table 3), with P. amarus being the only sample in which all eleven were detected and had been all previously detected in other studies (Nahar et al, 2012;Molska et al, 2014;Qi et al, 2014), confirming that it was the major producer of lignans among the studied species. Seven lignans were detected in P. niruri but, only niranthin, hypophyllanthin and dextrobursehernin were detected for the first time (Nahar et al, 2012;Qi et al, 2014).…”
Section: Lignan Content In the Different Phyllanthus Speciessupporting
confidence: 71%
“…Analysis of the P. niruri sample in different columns showed that the DB-35 and DB-17HT columns have a greater discrimination capacity for lignans than the DB-5ms column, similar to that used by Molska et al (2014) (Figure 2). The higher content of phenyl groups in these columns allows for a better interaction of the lignans with…”
Section: Chromatographic Methods Developmentmentioning
confidence: 61%
See 2 more Smart Citations
“…Each group was treated orally “gavage” with either 750, 1000, 1250 or 1500 mg/kg of each leave extract. The dose range was selected based on earlier studies; where oral doses of Moringa peregrina aqueous and ethanolic seed extract ranging between 100-300 mg/kg were found to be safe yet potent as anti-inflammatory [ 12 ]. Also, based on the fact that the i.p.…”
Section: Methodsmentioning
confidence: 99%